The current national (state) bibliography of the subjects of the Russian Federation - G. L. Levin (Библиосфера)
The main stages of forming the system of the current state (national) bibliographic control in the subjects of the Russian Federation since the 1930s are considered. The current state in the system of accounting of bibliographic resources, reflecting its results is analyzed. The ways of improving the state bibliographic indexes of the Russian Federation subjects in new technological conditions are proposed.